Pengolahan Sampah Organik dan Limbah Biomassa dengan Teknologi Olah Sampah di Sumbernya - I Made Indradjaja M. Brunner; Arief Norhidayat; Satria M. Brunner (Fakultas Teknik, 2021)
Solid Waste Processing Technology at the Source (TOSS) is an alternative method in processing organic and biomass waste on a communal scale. The processing of organic and biomass waste material is carried out in three stages of the process: biodrying which utilizes the aerobic activity of microorganisms; chopping which is intended to refine the material, and pelletization to compact the material into biomass pellets. The biodrying process in bamboo boxes is able to reduce the water content in organic and biomass waste within 4-5 days. Sorting of non-organic materials can be done at an early stage before or after the biodrying process. Sorting is required before chopping and pelletizing process to avoid unnecessary machine break down. The biomass pellet which is the final product has a diameter of about 10 mm with a length between 10-40 mm, a calorific value between 3000-4000 kcal/kg, and a moisture content of up to 15%. Compared to coal, biomass pellets tend to have higher volatile and ash content, while lower ash and sulfur content.